2016
DOI: 10.1021/acs.nanolett.5b04613
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Disorder in Black Phosphorus and Monochalcogenide Monolayers

Abstract: Ridged, orthorhombic two-dimensional atomic crystals with a bulk Pnma structure such as black phosphorus and monochalcogenide monolayers are an exciting and novel material platform for a host of applications. Key to their crystallinity, monolayers of these materials have a four-fold degenerate structural ground state, and a single energy scale E C (representing the * To whom correspondence should be addressed † Department of Physics. elastic energy required to switch the longer lattice vector along the x− or y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
171
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(182 citation statements)
references
References 53 publications
11
171
0
Order By: Relevance
“…Further modeling of the nanosculpting effect would require a systematic study of electron-beam-induced disorder in BP 38 in addition to thermally induced defects. 39 …”
Section: Resultsmentioning
confidence: 99%
“…Further modeling of the nanosculpting effect would require a systematic study of electron-beam-induced disorder in BP 38 in addition to thermally induced defects. 39 …”
Section: Resultsmentioning
confidence: 99%
“…The energy curve for SnS has a minimum rather than a saddle point at Cmcm-ML, and therefore resembles a ferroelectric with first order phase transition, with the peculiarity that the Cmcm-ML structure is stable for all T > 0. Recently, based on Car-Parrinello molecular dynamics simulations, Mehboudi et al showed that monolayer monochalcogenides undergo an order-disorder phase transition [31]. Hence, since SnS and GeSe have four degenerate P nma-ML phases, we expect that the average total polarization goes to zero as temperature approaches T m .…”
Section: Application Of Electric Fieldmentioning
confidence: 96%
“…vdW-DF-cx has already proven itself accurate and useful in a number of problems that involve both regions of sparse and dense electron distributions such as molecular dimers [16,40], layered materials [9,[41][42][43][44][45], semiconductors [9,46], molecular crystals [47,48], adsorption processes [21,49], as well as weak chemisorption, molecular switching, and molecular selfassembly [21,49,50]. The ACF foundation and the emphasis on conservation laws in the vdW-DF-cx construction further suggests a general-purpose nature [9] and motivates a comprehensive investigation of its performance also for regular dense matter.…”
Section: Introductionmentioning
confidence: 99%